COSMIC INTELLIGENCE DALAM PERSPEKTIF SUFISTIK:STUDI ATAS PEMIKIRAN RD. AAS RUKASA - Moh. Washil; Masykur Arif (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
Today is the age of technology that provides facilities in the form of comfort and convenience for human life. This era can be called the peak of human glory. Along with this, humans also show serious problems in various fields of life, such as environmental crises, the emergence of new diseases and viruses, crime, and natural disasters which are ongoing problems with the peak of that glory. In this absurd situation, humans need a new perspective on life. Aas Rukasa in Cosmic Intelligence brings this new paradigm to society, an ecological perspective on life by empowering the capacity of cosmic intelligence. By using the approach of Sufism, Abdul Karim al-Jili and Amin Syukur, this research aims to read the Cosmic Intelligence book regarding what teachings contain Sufi values and how to implement them in everyday life to overcome this absurdity. This research resulted in the finding that for Aas Rukasa cosmic intelligence will be fully developed if a person utilizes meditation and breathing exercises in everyday life. In addition, the world is not seen as a barrier to spiritual progress, instead, the world becomes a medium to improve the quality of one's closeness to God. The implementation of cosmic intelligence for Kang Aas is to bring the understanding gained in the cosmic field to everyday life. For this reason, several principles must be owned by someone in implementing their relation to building a new civilization, namely; having an independent spirit, originality, visionary, a clear vision and orientation, futuristic, adaptive to new things, paying attention to growth and development, has consistency, has integrity and has a leadership spirit